SAT0123 Radiographic Severity of Rheumatoid Arthritis in Latin American Patients: Results from The Gladar Cohort. (15th July 2016) - Massardo, L.; Schweitzer, F.; Pineda, C.; Pons-Estel, B.; Cardiel, M.; Soriano, E.; Galarza, C.; Levy, R.; Sacnum, M.; Caballero-Uribe, C.; Bianchi, W.; Gonzalez, H.; et al.
Abstract : Background: More radiographic damage occurs within the first year of rheumatoid arthritis (RA). Erosions occurring preferentially in feet and joint space narrowing (JSN) in wrists have been described in early RA. Little is known of radiographic progression in Latin American patients with early RA. Objectives: To describe radiographic changes in a Latin American (LA) early rheumatoid arthritis (RA) multinational inception cohort at baseline, a multicenter observational study. Methods: Patients were enrolled in GLADAR ( Grupo Latino Americano de estudio De Artritis Reumatoide), the largest longitudinal cohort of early RA (<1 year from onset) in LA, from 2004/2005–2008. Demographic and clinical data were obtained and sets of hand/wrist and foot radiographs were scored using the modified Sharp/ Van der Heijde scoring system. Results: A total of 507 patients with radiographic readings were evaluated. The mean radiographic score was 23.37 at baseline visit; 56.2% had erosions and 97.8% joint space narrowing (JSN). Among patients with JSN, the mean score was 20.97. JSN occurred in hands/wrists (97%) and feet (72%), while erosions were observed in hands/wrists (42.8%) and feet (28.8%). X-rays of 253 patients were assessed after at one-year of follow-up; of 132 without erosions, 14.4% developed erosions; and 100% JSN. No significant differences were observed among patients who progressed according to socio-demographic features, use of DMARDS, use of prednisone and rheumatoid factor positivity. Conclusions: This is the largest radiographic study of Latin American RA patients. Damage occurs early in the disease. Surprisingly, JSN is the most common radiographic change and occurs more often in hands/wrist. Further studies are needed to understand the meaning of the greater breakdown in cartilage compared to erosions in this population. References: Loreto Massardo, Bernardo A. Pons-Estel, Daniel Wojdyla, Mario H. Cardiel, C. Pineda, E. R. Soriano et al; GLADAR. Early Rheumatoid Arthritis in Latin America: Low Socioeconomic Status Related to High Disease Activity at Baseline. Arthritis Care & Research Vol. 64, No. 8, August 2012, pp 1135–1143 Cardiel M.H., Pons-Estel B.A., Wojdyla D., Saurit V., Marcos JC., Pinto MR., Cordeiro de Azevedo A.B., da Silveira I.G., Radominski S.C., Ximenes A.C., Massardo L., Ballesteros F., Rojas-Villarraga A., Oñate R.V., Hernandez M.P., Esquivel-Valerio J.A., García-De La Torre I., Khoury V.J., Millán A., Soriano E.R.; GLADAR. Treatment of early rheumatoid arthritis in a multinational inception cohort of Latin American patients: the GLADAR experience. J Clin Rheumatol. 2012 Oct;18(7):327–35. Disclosure of Interest: None declared